The Shelf Registration of Debt and Self Selection Bias. - Allen, David S; Lamy, Robert E; Thompson, G Rodney (Journal of Finance, 1990)
Prior studies report lower issue costs for shelf registered debt and conclude that the benefits of increased underwriter competition can be realized by those firms using this registration procedure. This study reexamines the purported superiority of issuing debt via shelf registration, and finds that the savings in issue costs displayed by earlier studies can be attributed to a self-selection bias and not the method of registration.